2023
DOI: 10.3390/life13061368
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Contrast-Enhanced Magnetic Resonance Imaging in Uterine Cervical Cancer: A Systematic Review

Giacomo Avesani,
Alessio Perazzolo,
Andrea Amerighi
et al.

Abstract: Correct staging of cervical cancer is essential to establish the best therapeutic procedure and prognosis for the patient. MRI is the best imaging modality for local staging and follow-up. According to the latest ESUR guidelines, T2WI and DWI-MR sequences are fundamental in these settings, and CE-MRI remains optional. This systematic review, according to the PRISMA 2020 checklist, aims to give an overview of the literature regarding the use of contrast in MRI in cervical cancer and provide more specific indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 113 publications
0
0
0
Order By: Relevance
“…Studies have shown that tumours demonstrating lower enhancement (poorly perfused hypoxic tumours are linked to increased aggressiveness, increased risk of metastasis, and treatment failure) had a poorer response to therapy and a lower survival rate. However, the studies did not identify a precise, reproducible value for those parameters, limiting their use in current clinical practice [28].…”
Section: Mri Protocol For Uterine Cervical Cancermentioning
confidence: 96%
See 1 more Smart Citation
“…Studies have shown that tumours demonstrating lower enhancement (poorly perfused hypoxic tumours are linked to increased aggressiveness, increased risk of metastasis, and treatment failure) had a poorer response to therapy and a lower survival rate. However, the studies did not identify a precise, reproducible value for those parameters, limiting their use in current clinical practice [28].…”
Section: Mri Protocol For Uterine Cervical Cancermentioning
confidence: 96%
“…A systematic review by Avesani et al did not find strong evidence to indicate contrast-enhanced (CE) sequences to be helpful in the initial staging or the detection of tumour recurrence and did not find CE-MRI could provide any additional information than that obtained from DWI sequences [28]. Combined chemoradiotherapy is the treatment of choice for large cervical cancers.…”
Section: Mri Protocol For Uterine Cervical Cancermentioning
confidence: 99%